Obligacja "bycza" i "niedźwiedzia" jako instrument inwestowania i pozyskiwania kapitału - Mamcarz, Henryk (Bull and Bear Bond as an Instrument of Raising and Investing Capital, 2007)
Bull and bear bond belongs to a group of indexed bonds in which case the indexation base is the specific stock exchange index. The issue of these bonds is carried out in two big, equal tranches: bull tranche and bear tranche. Due to the low interest coupon, the issue is a cheap way of raising the capital for the issuer. At the same time the issue gives to the investor a possibility of realizing speculative and hedging strategies at both increasing and going down stock prices. Exchange bonds prices are determined by changes in the interest rate at the capital market and changes of the stock exchange index. The condition of the correct functioning of bull and bear bond is high liquidity of the secondary market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 355-364